INTERPRETASI TEOREMA PERMAINAN TANDA PADA LAGU THIS IS WAR OLEH “30 SECONDS TO MARS” - Aswin Panembrama (Saraswati)
This Is War is a song popularized By 30 Seconds To Mars. This Is War is a progressive rock genre songs that lasted 5 minutes 27 seconds. Music can not be separated from elements outside the musical elements. lyrics of 30 Seconds To Mars talk about humanism and global social by using the concept of the philosophical literature. The song This Is War presented the semiotic signs, which is interesting to be correlated with the music in a study. Interpretation is the content of the science of hermeneutics. Interpretation of signs studied in the field of semiotics. Semiotic theory are used in the interpretation of the song This Is War is the theory of Charles Sanders Peirce Three Trichotomy. During the study of music and semiotics in Indonesia is still not prevalent. This study is a musicological study using descriptive analysis qualitative-interpretative through the lens of semiotics-hermeneutical. The purpose of this thesis describes the analysis and interpretation of the song transforms This Is War to be a reference study of semiotics-hermeneutical and musicologist who has been there, as well as opportunities for music outside the academic context has feasibility. The results of this study stated that the interpretation of the music is composed of the signs that are relevant in the context of the relevant musical and narrative life. By interpreting the signs, the music Keyword: This Is War, Interpretation, Semiotic